EFFECTIVENESS OF HEALTH EDUCATION WITH FLIPCHART MEDIA ON IMPROVING QUALITY OF LIFE AND DIET COMPLIANCE IN HYPERTENSION PATIENTS - Yobel, Sosilo; Kristiani, Rina Budi (jfpublisher, 2023)
Introduction. The problem is, there are still many hypertension sufferers who don't take care of their diet that which can affect the condition and lead to complications that impact on quality of life. The purpose of this study was to determine the effectiveness of health education using flipchart media to improve quality of life and dietary compliance in hypertensive patients. Method. This research is a pre-experimental study with the